2016
DOI: 10.14744/nci.2016.26023
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of sTREM-1 and procalcitonin levels in the early diagnosis of sepsis

Abstract: OBJECTIVE:Sepsis is still major cause of morbidity and mortality, despite improvements in diagnosis and treatment in modern medicine. Therefore, laboratory examinations that provide correct and rapid results are needed to support the diagnosis. This study was conducted to investigate value of immunological indicators procalcitonin (PCT) and soluble triggering receptor expressed on myeloid cells-1 (sTREM-1) in differential diagnosis of patients with sepsis and systemic inflammatory response syndrome (SIRS), as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 32 publications
0
11
0
3
Order By: Relevance
“…In the remaining 385 abstracts, full manuscripts were recruited for further assessment, and 366 articles were excluded with reasons. A final of 19 studies were included in this meta-analysis [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] (Fig. 1).…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the remaining 385 abstracts, full manuscripts were recruited for further assessment, and 366 articles were excluded with reasons. A final of 19 studies were included in this meta-analysis [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] (Fig. 1).…”
Section: Study Selectionmentioning
confidence: 99%
“…A total of 2418 patients was finally enrolled in this meta-analysis, with the average sepsis prevalence of 60.3%. Among the 19 studies included, 17 were prospective [14,15,17,[19][20][21][22][23][24][25][26][27][28][29][30][31][32] and two were cross-sectional [16,18]; in five studies traumatic or post-operative patients were enrolled exclusively [16,19,22,28,29]. Pulmonary infection was the leading cause of infection in 14 studies.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gibot et al (2007) reported that measurement of serum PCT together with s-TREM-1 concentrations could be useful for detecting nosocomial sepsis. Aksaray et al (2016) also reported that s-TREM-1 and PCT are excellent markers for early diagnosis of sepsis. Although further studies are required to confirm them, our preliminary findings indicate that s-TREM-1 could enable postmortem diagnosis of sepsis with good sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 95%
“…A soluble form of TREM-1 (sTREM-1) is released from activated phagocytes and can be found in serum [15]. The plasma level of sTREM-1 appears to be a reliable parameter in differentiating patients with sepsis from those with SIRS [16,17]. However, application of sTREM-1 for the early diagnosis of LC patients with SIRS has not been done.…”
Section: Introductionmentioning
confidence: 99%